2016
DOI: 10.4103/2231-0762.178747
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the accuracy of implant master casts fabricated from two different transfer impression techniques

Abstract: Aim:This study evaluated and compared two impression techniques in terms of their dimensional accuracies to reproduce implant positions on working casts.Materials and Methods:A master model was designed to simulate a clinical situation. Impressions were made using four techniques: (1) Stock open tray (SOT) technique; (2) stock closed tray (SCT) technique; (3) custom open tray (COT) technique; and (3) custom closed tray (CCT) technique. Reference points on the hexagonal silhouette of the implant on master model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 19 publications
4
29
0
Order By: Relevance
“…3,9,12 Searching for decreasing the errors in the impression of multiple implants, the literature reports new techniques, such as the direct splinting impression, whose main goal is to link the transfer copings so that no distortion occurs inside the impression. 3,9,16 Currently, different methods are used to splint the copings: acrylic resin with dental floss, 2,[6][7][8]9,[17][18][19][20][21] premanufactured resin bar, 1,[3][4]25 plaster, 11 and composite resin. 2,8 The self-cured acrylic resin is the method of choice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3,9,12 Searching for decreasing the errors in the impression of multiple implants, the literature reports new techniques, such as the direct splinting impression, whose main goal is to link the transfer copings so that no distortion occurs inside the impression. 3,9,16 Currently, different methods are used to splint the copings: acrylic resin with dental floss, 2,[6][7][8]9,[17][18][19][20][21] premanufactured resin bar, 1,[3][4]25 plaster, 11 and composite resin. 2,8 The self-cured acrylic resin is the method of choice.…”
Section: Discussionmentioning
confidence: 99%
“…3 The use of customized trays show better results than that of conventional trays because of the uniform thickness of the first, which assured a uniform thickness of the impression material. 6 The literature reports sixteen studies using customized trays [1][2]4,[6][7]9,[11][12][18][19][20][21][22]25,26 and seven using conventional trays. 1,3,5,8,11,13,21 Furthermore, nine studies compared the direct with the indirect technique, and almost unanimously they reported better results with the open tray technique, 6,[11][12][15][16][17]24,27 except for one study that reported no statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations